PENGARUH KUALITAS PELAYANAN DAN BAURAN PEMASARAN MELALUI VARIABEL MEDIASI WORD OF MOUTH TERHADAP MINAT MASUK PONPES : Study Kasus Pada Pondok Pesantren Addinuriyah Dua Kecamatan Pedurungan Kota Semarang - Khoirurrofik, Fathur; Kurniawan, Bayu; Indriasari, Ika (Lembaga Pengembangan Kinerja Dosen, 2023)
Abstract The purpose of this study was to analyze the effect of service quality and marketing mix through the Word of Mouth variable on interest in entering Islamic boarding schools (a case study at the Addainuriyah Dua Islamic Boarding School in Semarang) using the random sampling method on 167 students for the 2023 academic year. PLS-SEM (Partial) data analysis technique Least Square-Structural Equation Model) using the SmartPls 4.0 tool. The results showed that service quality had no effect on word of mouth, marketing mix had a significant positive effect on word of mouth, word of mouth had a significant positive effect on interest in entry, service quality had a significant positive effect on interest in entry, marketing mix had a positive effect Significantly on Intention to Enter, Service Quality mediated by Word Of Mouth has no effect on Intention to Enter, Marketing mix mediated by Word Of Mouth has a significant positive effect on Intention to Enter.